2016
DOI: 10.1097/mrr.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Chinese version of the Daily Living Self-Efficacy Scale among stroke patients

Abstract: The aim of this study was to examine the reliability and validity of the Chinese version of the Daily Living Self-Efficacy Scale (DLSES) in stroke patients. In total, 172 participants were recruited from a local hospital in China. The internal consistent reliability and convergent validity of the total scale and activities of daily living (ADL) and psychosocial functioning subscales were examined and factor analysis was carried out. Cronbach's αs for the Chinese version of the DLSES, ADL subscale, and psychoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Usually, an acceptable overall follow-up rate is considered to be 80% or more of participants whose exposures were measured at baseline. In 6 studies, 27,38,40,42,54 this percentage was lower than 20%. Only in 13 [25][26][27]29,30,32,33,[41][42][43]50,51,58 studies were key potential confounding variables measured and adjusted for, such as by statistical adjustment for baseline differences; in other studies this process was not reported.…”
Section: Study Populationmentioning
confidence: 84%
See 4 more Smart Citations
“…Usually, an acceptable overall follow-up rate is considered to be 80% or more of participants whose exposures were measured at baseline. In 6 studies, 27,38,40,42,54 this percentage was lower than 20%. Only in 13 [25][26][27]29,30,32,33,[41][42][43]50,51,58 studies were key potential confounding variables measured and adjusted for, such as by statistical adjustment for baseline differences; in other studies this process was not reported.…”
Section: Study Populationmentioning
confidence: 84%
“…The assessment of the studies through the QAT provided a more specific overview of the quality of the studies tracked by the review. Only 16 25,28,31,32,34,36,42,43,[47][48][49][50][51][52][53]62 of the 39 studies were published after the publication of the COSMIN checklist and these guidelines were not followed in the majority of the included studies; however, according to the QAT, the studies published after 2010 do seem to have higher quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations